Decreased plasma tryptophan associated with deep white matter lesions in elderly subjects. Issue 1 (1st January 1999) - Yao, H; Yuzuriha, T; Koga, H; Fukuda, K; Endo, K; Matsumoto, T; Kato, A; Uchino, A; Ezaki, T; Ibayashi, S; Uchimura, H; Fujishima, M
Abstract : The aim was to identify potentially treatable risk factors for cerebral white matter lesions often found on MRI in elderly persons. findings were assessed on 1.0 T MRI of 178 subjects living in the community and aged 60 years or older. Participants underwent standardised evaluations including standard questionnaires, a physical and neurological examination, cognitive function tests, electrocardiogram, a complete blood chemistry panel, and plasma amino acid measurements. Brain MRI infarcts, deep white matter lesions (DWMLs), and periventricular hyperintensities were found in 26%, 43%, and 29% of the 178 participants, respectively. Subjects with DWMLs were significantly older and had a higher frequency of hypertension, higher systolic blood pressure, and more brain infarcts, but lower plasma concentrations of tryptophan. In the multivariate model, greater age and lower plasma tryptophan concentrations were independently associated with DWMLs. Tryptophan concentrations were inversely related to DWML grading, whereas hypertension and brain infarction were more common in subjects with higher extents of DWMLs. The present study suggests that greater age and lower plasma tryptophan concentrations were important in producing DWMLs in elderly subjects.